2022
DOI: 10.3390/nano12050781
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Electrochemical Detection Electrodes for As(III)

Abstract: Arsenic is extremely abundant in the Earth’s crust and is one of the most common environmental pollutants in nature. In the natural water environment and surface soil, arsenic exists mainly in the form of trivalent arsenite (As(III)) and pentavalent arsenate (As(V)) ions, and its toxicity can be a serious threat to human health. In order to manage the increasingly serious arsenic pollution in the living environment and maintain a healthy and beautiful ecosystem for human beings, it is urgent to conduct researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 216 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…This gives a clue that a graphene-based electrode could possibly be a low-cost, high-performance solution for the As(III) sensor in the absence of expensive Pt and Au. Recent advances in As(III) electrochemical sensing approaches have been summarized in [ 14 ]. However, there has been no report of using microporous graphene foam with nanoflowers as an electrode for As(III) sensing, which will be reported in this work.…”
Section: Introductionmentioning
confidence: 99%
“…This gives a clue that a graphene-based electrode could possibly be a low-cost, high-performance solution for the As(III) sensor in the absence of expensive Pt and Au. Recent advances in As(III) electrochemical sensing approaches have been summarized in [ 14 ]. However, there has been no report of using microporous graphene foam with nanoflowers as an electrode for As(III) sensing, which will be reported in this work.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the potential utility of a diverse range of materials, including bulk/ nanophase phase metals and other materials such as carbon nanoparticles, noble MNPs, metal oxide nanoparticles, and bimetallic nanoparticles including biomaterial-modified electrodes, for the electrochemical sensing of arsenic has been tested. 13 Li et al 17 have reported an intriguing application of the Au−Fe 2 O 3 nanocomposite surface-confined Fe(II)/Fe(III) redox pair in facilitating the electrochemical detection of As(III). With the aim to mimic this wonder material, Prussian blue (PB), a bimetallic coordination compound has been extensively investigated for its catalytic and electrocatalytic aspects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To solve this problem, graphene and derivatives of graphene (functionalization, modification and recombination of graphene) have received significant attention in the area of electrochemistry, because of graphene have excellent properties such as high‐speed electron mobility, large surface area, and high electrical conductivity [10–19] . Over the recent decade various graphene based electrode materials such as noble metal/graphene, metal oxide/graphene, conductive polymer/graphene used towards electrochemical detection of As ions with high sensitivity and high electrode stability [20] . Among these strategies, graphene surface covalently functionalization with organic heterocyclic compounds [21] for electrode material is one of the most extensively investigated and it has proven to be a highly effective method.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Over the recent decade various graphene based electrode materials such as noble metal/graphene, metal oxide/graphene, conductive polymer/ graphene used towards electrochemical detection of As ions with high sensitivity and high electrode stability. [20] Among these strategies, graphene surface covalently functionalization with organic heterocyclic compounds [21] for electrode material is one of the most extensively investigated and it has proven to be a highly effective method. The organic heterocyclic compound functionalized with graphene has been widely used for metal ion detection in recent decades.…”
Section: Introductionmentioning
confidence: 99%